Personality alchemy: The influence of personality traits on the circular entrepreneurial intentions of higher education students - Sofia Gomes; Micaela Moreira Pinho; Jo\~ao M. Lopes (Entrepreneurial Business and Economics Review (EBER), 2025)
Objective: The study explores the influence of Portuguese higher education students' personality traits on their intentions to become circular entrepreneurs using their perceived circular behavioural control as a mediator. We considered internal locus control, proactive personality, perceived creativity and propensity to take risks as personality traits. Research Design & Methods: We used an online questionnaire to collect data from 510 Portuguese university students. We performed the quantitative analysis through the partial least square method. Findings: We found that the propensity to assume risk, creativity, internal locus of control, and proactivity were (by these order) personality traits with a positive influence on either respondents' circular behavioural control and, using this, their circular entrepreneurs' intention. Implications & Recommendations: The results of this study allowed us to infer implications for higher education students, universities, and policymakers. Students demonstrated intentions to promote circular entrepreneurial activities, and these intentions can be worked on and learned at universities by encouraging creativity, innovation, and proactivity and inciting greater levels of confidence in students. These skills allow you to accelerate the implementation of circularity in new businesses. To achieve this, greater coordination with the business community is essential by proposing challenges and problems that universities can help resolve. Political decision-makers must formulate circular entrepreneurship policies and include them in the national development plan, encouraging the formulation of new sustainable businesses. Contribution & Value Added: This study highlights the relationship between personality traits and the intention to become a circular entrepreneur, providing novel evidence in this field. Moreover, it introduces perceived circular behavioural control as a mediator between personality traits and entrepreneurial intentions, an innovative approach in empirical research models. These insights can contribute to the development of policies and strategies aimed at fostering circular entrepreneurship, helping to create environments more conducive to sustainable innovation and economic development based on resource reuse and regeneration.
Keywords: L26; Q56; 330; circular entrepreneurship; circular entrepreneurial intention; personality traits; perceived circular behavioural control; higher education students